1993
DOI: 10.1002/hup.470080403
|View full text |Cite
|
Sign up to set email alerts
|

State‐dependent retrieval and midazolam

Abstract: This experiment investigated the phenomenon of state-dependent retrieval with midazolam by comparing performance after midazolam + placebo with that after reversal with the benzodiazepine antagonist flumazenil, in tests of explicit and semantic memory and judgements of remncy. The subjects completed analogue rating scales and psychomotor tests to provide measures of sedation. Midazolam (0.05 mg/kg) impaired recall and recognition of pictures and performance in the digit-symbol substitution task. There were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…This means a change from a relatively highly drugged state to a low or non-drugged state or reverse. It has been reported that state change from BZD drug to placebo condition may negatively affect on memory retrieval in comparison to continuous BZD condition [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means a change from a relatively highly drugged state to a low or non-drugged state or reverse. It has been reported that state change from BZD drug to placebo condition may negatively affect on memory retrieval in comparison to continuous BZD condition [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a result would provide evidence that implicit and explicit memory are mediated by different memorial factors. 1 Studies using the benzodiazepine antagonist flumazenil have shown evidence inconsistent with the hypothesis that midazolam amnesia is due to a state-dependent memory effect in free recall (Birch & Curran, 1990;File, Goodall, Mabbutt, Harris, & Skelly, 1993). Specifically, such studies show that although flumazenil reverses midazolam's major sedative effects (e.g., psychomotor performance returns to normal levels), midazolam's amnesic effects remain, and are as strong as in a condition where participants are administered an injection of saline prior to free recall.…”
Section: Characteristics Of Midazolam Amnesiamentioning
confidence: 93%
“…Diazepam-induced place preference was not state dependent (Overton 1984) because a spatial bias was measured in the absence (probe trial 1 in experiment 2B) and presence (probe trial 2 in experiment 2B) of the drug. State-dependent alterations in learning are well established for benzodiazepines (File et al 1993). …”
Section: Place Preference With Diazepammentioning
confidence: 98%